Pediatric Bartter syndrome: The therapeutic challenge - Aamir Jalal Al Mosawi (Archives of Clinical Nephrology - Peertechz Publications, 2020)
Background: There is no curative therapy for many of the rare genetic disorders such as Bartter syndrome. Many patients with such disorders will be treated to a large extent with symptomatic therapies, and many of them will continue to have some symptoms, and growth and mental retardation despite the traditional therapies generally known by the treating physician. Because of the rarity of such disorders, many specialist physicians may have limited experience with treatment of such disorders and treatment side effects may be sometimes encountered. It is hoped that advances arising from the accumulating research evidence can contribute to improving treatment of such conditions. Materials and methods: A unique case of classical pediatric Bartter syndrome associated with low set ears and mental retardation that was treated unsatisfactorily was studied. The medical literatures were reviewed for the recent research evidence that may help in improving the therapeutic services for patients with Bartter syndrome. Results: The occurrence the rare genetic disorder Bartter syndrome in Iraq has not been documented. A unique case of Bartter syndrome associated with low set ears and mental retardation in an Iraqi girl. The girl was treated before referral by some of the traditional therapies that improved her symptoms and condition, but she experienced some side effects of treatment and growth and mental retardation. Conclusion: Literature review helped in recommending an evidence-based opinion suggesting the replacement of one drug with a safer one, and the addition of another evidence-based effective therapy.